Optimization of Fused Deposition Modeling (FDM) Machine Process Parameters for Polylactic Acid (PLA) Surface Roughness Using the Taguchi Approach - Rosyadi, Mochammad Willdan; Prayoga, Adimas Dwi; Mukti, Abdi Satryo; Mahameru, Rolland Darin Khalifah; lestari, Wahyu Dwi (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2024)
The surface quality of 3D printed products greatly influences the performance and aesthetics of the final product. Polyalactid Acid (PLA) is a material commonly used in 3D printing manufacturing because it is environmentally friendly and easy to use. However, the roughness of the printed surface is often a challenge that needs to be overcome to improve product quality. This research aims to optimize surface roughness in the 3D printing process using PLA material by applying the Taguchi method. The 3D printing parameters used in this research are nozzle temperature, infill density, printing speed, layer thickness, infill pattern, and orientation with each parameter having three levels. The research results show thatThe optimal parameter combination that produces the lowest surface roughness is nozzle temperature at level 2, infill density at level 3, printing speed at level 3, layer thickness at level 3, infill pattern at level 3, and orientation at level 3. The use of the Taguchi method also shows that the combination of printing process parameters is the factor that most influences the quality of the printed surface. With this optimization, it is hoped that it can improve the quality of 3D printed products and expand the application of PLA materials in various industries.